Discovery of Triterpenoids as Reversible Inhibitors of α/β-hydrolase Domain Containing 12 (ABHD12) - Parkkari, Teija; Haavikko, Raisa; Laitinen, Tuomo; Navia-Paldanius, Dina; Rytilahti, Roosa; Vaara, Miia; Lehtonen, Marko; Alakurtti, Sami; Yli-Kauhaluoma, Jari; Nevalainen, Tapio; Savinainen, Juha R.; Laitinen, Jarmo T. (PLOS ONE, 2014)
Background α/β-hydrolase domain containing (ABHD)12 is a recently discovered serine hydrolase that acts in vivo as a lysophospholipase for lysophosphatidylserine. Dysfunctional ABHD12 has been linked to the rare neurodegenerative disorder called PHARC (polyneuropathy, hearing loss, ataxia, retinosis pigmentosa, cataract). In vitro, ABHD12 has been implicated in the metabolism of the endocannabinoid 2-arachidonoylglycerol (2-AG). Further studies on ABHD12 function are hampered as no selective inhibitor have been identified to date. In contrast to the situation with the other endocannabinoid hydrolases, ABHD12 has remained a challenging target for inhibitor development as no crystal structures are available to facilitate drug design. Methodology/Principal Findings Here we report the unexpected discovery that certain triterpene-based structures inhibit human ABHD12 hydrolase activity in a reversible manner, the best compounds showing submicromolar potency. Based on structure activity relationship (SAR) data collected for 68 natural and synthetic triterpenoid structures, a pharmacophore model has been constructed. A pentacyclic triterpene backbone with carboxyl group at position 17, small hydrophobic substituent at the position 4, hydrogen bond donor or acceptor at position 3 accompanied with four axial methyl substituents was found crucial for ABHD12 inhibitor activity. Although the triterpenoids typically may have multiple protein targets, we witnessed unprecedented selectivity for ABHD12 among the metabolic serine hydrolases, as activity-based protein profiling of mouse brain membrane proteome indicated that the representative ABHD12 inhibitors did not inhibit other serine hydrolases, nor did they target cannabinoid receptors. Conclusions/Significance We have identified reversibly-acting triterpene-based inhibitors that show remarkable selectivity for ABHD12 over other metabolic serine hydrolases. Based on SAR data, we have constructed the first pharmacophore model of ABHD12 inhibitors. This model should pave the way for further discovery of novel lead structures for ABHD12 selective inhibitors.